2017
DOI: 10.1111/coa.12813
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary sinus volume: new physiopathological data in fungal ball genesis? A retrospective study

Abstract: This study suggests that maxillary fungal ball is associated with a smaller size of the affected MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…This result was in line with that of a research conducted by Kim et al, who reported a relationship between a decreased MSV and persistent chronic rhinosinusitis in young patients. The side effect of reduced MSV could be the development of a maxillary sinus fungal ball 22 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…This result was in line with that of a research conducted by Kim et al, who reported a relationship between a decreased MSV and persistent chronic rhinosinusitis in young patients. The side effect of reduced MSV could be the development of a maxillary sinus fungal ball 22 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are only a few reports evaluating the relationship between the volume of MS and the presence of unilateral MSFB (17) . Michel et al reported that there was a significant statistical difference in volume between diseased MS and disease-free MS in the FB group (17) . In addition, a FB was found in the smallest MS of the FB group (93%).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a FB was found in the smallest MS of the FB group (93%). They suggested that MSFB was associated with a smaller size of MS (17) . In our study, the volumes of both MSs were not statistically different (p>0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Their size may be correlated with the occurrence of obstructive sleep apnea, the genesis of antrochoanal polyps, and fungal infections. Despite their location and function, the thorough radiological assessment of the morphology of the MS pre- and postoperatively is not a standard routine in patients undergoing surgical procedures involving the LeFort I osteotomy [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%